PENGARUH SISTEM HUKUM COMMON LAW TERHADAP SISTEM HUKUM INDONESIA - Doni Joremenda; Putri Jesika Yolanda; Dina Pratiwi Br Tambun (JOURNAL SAINS STUDENT RESEARCH, 2024)
Indonesia as a legal country adheres to a legal system influenced by colonial countries, namely the Netherlands which adheres to the Continental European legal system or Civil Law System. The aim of this research is to determine the influence of the common law legal system on the Indonesian legal system. This research uses legal research with a normative juridical approach. The research results show that the influence of the common law legal system on the legal system in Indonesia is much related to economic activities, including business contracts, court decision making is also affected by this legal system, such as arbitration and commercial advertising in resolving contract disputes. Meanwhile, regarding the influence of common law in business contracts in Indonesia, it can be seen from the first entry of foreign capital. The implementation of legal institutions originating from the Common Law legal system in Indonesia which adheres to the Civil Law legal system shows that there is a situation of mixed legal systems (mixed jurisdiction). With the entry of the Common Law legal system into Indonesia's economic institutions, the law requires adjustments because the law must provide legality for all changes that occur.